(3hajGJ GdCYjGf hCfHGA CHfGA GdReGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s
(3ChdgG (B:s
(3MQa GdgGA JQLeI GdTQja CHj GdSYGOGJ gHg Gddg GdeYQha HGHf GdGTLQi GdHZOGOi s
(3BNQgG (B:s
(3BNQg JQLeI jhfS Hf YHO GdCYdi , CHh ehSi s
(3GdLRA GdQGHY ef fSNI CNQis
(3ChdgG hBNQgG HNW eZGjQ CMOKs
(3cJHJ GdYfGhjf HGdMeQIs
(3HChdgG JedjcGJ s
(3Ydi MhGTjgG HYV GdJYdjbGJ s
(3GdfSNI HgG MhGT s
Keywords: (3GdJGQjNs